Tax competition, capital mobility, and innovation in the public sector - Michael Rauscher (Universität Rostock, Institut für Volkswirtschaftslehre, 2005)
The paper analyses the impact of tax competition on innovation in the public sector. It is shown that the effects of increased mobility of the tax base on innovation and growth are ambiguous. The negative relationship is more likely, however. Moreover, it is shown that a Leviathan government may be induced to spend a larger share of its budget on unproductive activities.
Keywords: H21; H7; O31; O41; 330; tax competition; economic growth; innovation; Leviathan competition; North-South model